Geometrically constrained self-assembly and crystal packing of flattened and aligned carbon nanotubes. (November 2015) - Downes, Rebekah D.; Hao, Ayou; Park, Jin Gyu; Su, Yi-Feng; Liang, Richard; Jensen, Benjamin D.; Siochi, Emilie J.; Wise, Kristopher E.
Abstract: While the mechanical properties of highly aligned carbon nanotube (CNT) thin films and their nanocomposites have been widely studied, the load transfer mechanisms and failure modes of aligned CNT composites have not been sufficiently explored and understood. In this research, super-aligned CNT thin films with a measured alignment fraction of up to 0.93 are fabricated by mechanical stretching. High concentration (50–60 wt% CNT) CNT reinforced bismaleimide (CNT/BMI) nanocomposites are fabricated from the aligned network to study mechanical properties and microstructures. Atomic resolution transmission electron microscopy (TEM) analysis reveal unusual CNT crystal packing and permit the observation of interesting structural features of the CNTs and their assemblages, including collapse, flattened packing, preferred stacking, folding and twisting phenomena, as well as CNT pullouts from bundles and the resin matrix. The large surface-to-surface contact areas between aligned and flattened nanotubes, driven by van der Waals interactions, give rise to a high density packing of the flattened CNTs in the nanocomposite, resembling a graphitic material. Molecular dynamics (MD) simulations are performed to model the packing structure and understand the dependence of density on the relative content of flattened nanotube and void space. The modeling results support the conclusions drawn from the experimental observations.